2011
DOI: 10.4018/jkm.2011070107
|View full text |Cite
|
Sign up to set email alerts
|

Community-Based Development of Knowledge Products

Abstract: International organizations and government agencies have developed and collected a wealth of knowledge resources relevant to poor communities; however, the people who need these resources most often do not know these materials exist or are unable to access or understand them. Electronic sources of knowledge materials and means of communication are rarely integrated with traditional methods of knowledge delivery. This paper addresses the issue of knowledge sharing with poor communities and presents a software t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Some challenges in knowledge management for poverty eradication are ensuring that the right information and knowledge are produced and delivered in the right format to a wide range of stakeholders, building on existing indigenous knowledge, strengthening capacity and taking a realistic approach to technologies (Food and Agricultural Organisation of the United Nations (FAO) 2016). Other possible challenges include too little or too much Poverty eradication information or data; lack of information and knowledge on key areas such as strategic project management; project planning; monitoring and evaluation; systematisation of lessons learnt; and geographical and language barriers (Mikolajuk, 2011). Chantarasombat et al (2010) identified leadership, culture and technology as the key success factors for knowledge management.…”
Section: Knowledge Management Strategies For Poverty Eradicationmentioning
confidence: 99%
See 3 more Smart Citations
“…Some challenges in knowledge management for poverty eradication are ensuring that the right information and knowledge are produced and delivered in the right format to a wide range of stakeholders, building on existing indigenous knowledge, strengthening capacity and taking a realistic approach to technologies (Food and Agricultural Organisation of the United Nations (FAO) 2016). Other possible challenges include too little or too much Poverty eradication information or data; lack of information and knowledge on key areas such as strategic project management; project planning; monitoring and evaluation; systematisation of lessons learnt; and geographical and language barriers (Mikolajuk, 2011). Chantarasombat et al (2010) identified leadership, culture and technology as the key success factors for knowledge management.…”
Section: Knowledge Management Strategies For Poverty Eradicationmentioning
confidence: 99%
“…The FAO has established a community of practice on food loss reduction amongst nations (FAO, 2016). Mikolajuk (2011) observed that a network of knowledge-sharing among known community-based knowledge nodes (offices/centres) can provide direct access to knowledge resources to diverse groups of users around the world and package these resources in the format and language appropriate to local context. Mikolajuk (2011) posits that by using the right language and context, most black local business individuals in South Africa lack the strong information literacy skills needed for using ICTs effectively (Mason and Tembo, 2015), as well as the right media (text, images, animations, voice and video).…”
Section: Knowledge Management Strategies For Poverty Eradicationmentioning
confidence: 99%
See 2 more Smart Citations